Immunomodulatory Roles of Cell Cycle Regulators - Laphanuwat, Phatthamon; Jirawatnotai, Siwanon (Frontiers in Cell and Developmental Biology, 2019)
Core cell cycle regulators, including cyclin-dependent kinases (CDKs), cyclins, and cyclin-dependent kinase inhibitors (CKIs), are known for their well-characterized roles in cell division. Several recent studies have shed light on the roles of these proteins in immune modulation. The development and activation of cells in the immune system take place not only during embryonic development but throughout the life of a multicellular organism. Cell cycle regulators are involved in the development of immune cells, partly as the machinery controlling the expansion and differentiation of the populations of immune cells. In addition, these proteins serve non-cell cycle functions. In this review, we summarize the emerging roles of cell cycle regulators in modulating functions of the immune system and discuss how they may be exploited as therapeutic targets.